Finite Element Analysis of Skirted Strip Footing Resting on Cohesive Slopes - Hanan Adnan Hassan; Hadeel Ammar Mohammed; Najwa wasife jassim; Mohammed Yousif Fattah; Noor S. Al-Hassnawi (Journal of Engineering and Sustainable Development)
The bearing capacity of footing with and without a skirt has been investigated using a series of finite element analyses using the Geo-slope program. Several models were conducted with varying skirt depths and slope crest lactations. The impact of slope inclination b, height H, and soil undrained shear strength Cu were also covered. The paper findings demonstrated that several factors significantly change the estimate of bearing capacity with great effectiveness that is ranging between 16.7% and 52.7% for D/B = 0.5, 1 and 1.5, and L/B (distance from edge slope/width of footing) = 0, 1, 4 and 8 respectively, and 18.2%, 36.4, 57.6%; 11.6%, 17.6%; 27.9%  kPa, for D/B (depth of skirt/width of footing) = 0.5, 1 and 1.5  and L/B = 0, 1, 4 and 8 respectively in case β=10° slope inclination with H/B =2 and Cu=60 kPa for D/B = 0.5, 1 and 1.5  and L/B  = 0, 1, 4 and 8 with Cu=20 kPa respectively in case β=10° slope inclination with H/B =2, also the critical L/ B ratio is 4. Beyond this value, the increase in bearing capacity became constant.